Optimization of concentric tube continuum robot based on accuracy and overall length of the robot via genetic algorithm - Atoosa Davarpanah; Mostafa Khazaee; Amin Moslemi; SE Khadem (Annals of Robotics and Automation - Peertechz Publications, 2020)
Concentric Tube Continuum Robot (CTR) is a group of continuum robots which is composed of concentric tubes that can be axially translated and rotated at the base relative to one another. Their inverse kinematic is challenging due to their redundancy. On the other hand, knowledge about the inverse kinematics of the concentric-tube continuum robot is essential for control purposes. There are many solutions for reaching to a specific target point because of the redundancy of these kinds of robots. In this paper, a new method for solving the inverse kinematics of these kinds of robots is presented. The most common type of these robots consisting of three tubes is considered for this study, and the genetic algorithm technique is employed to optimize the solution of this problem. Minimum energy principle equations are used in this method. It is assumed that the robot moves in a free space, so the environment force on this robot is neglected. Also, it is supposed that the curvature of each tube remains constant along the tube. According to the results, a small error of the order 0.01mm was observed using the presented method, which is acceptable for most applications. Finally, the parameters of robot is optimized with concentration on accuracy and the overall length of the robot, which is an important parameter for stability.